Madame Bovary de Monique Proulx et L’Apparition de Roland Bourneuf: Flaubert revisité par la nouvelle québécoise contemporaine - Vignes, Sylvie (Romanica Silesiana)
The article analyzes two short stories – “Madame Bovary” by Monique Proulx and “L’Apparition” by Roland Bourneuf. The author compares and contrasts the two texts, referring, at the same time, to their common “model” – Gustave Flaubert’s novel “Madame Bovary”. Key-words : Quebec; Monique Proulx; Roland Bourneuf; Flaubert; Emma Bovary; Salomé; Hérodias; short story; rewriting; hypertext; hypotext; literary myths